Vishnu with Lakshmi - 103 - Brig Ajai Singh (2022)
Image courtesy: Brig A.P. Singh - www.collectingmoment.in [Though it is a damaged sculpture, we can identify the gada (mace) and shankha (conch) on the two left hands of Vishnu.